Language Choice in the Interactions of A Korean Family in the Minari Movie: A Sociolinguistic Approach (English Language and Literature (JELL), 2026)
This study aims to identify language choice patterns (Korean and English) and analyze the social factors that influence them in the interactions of a Korean immigrant family (the Yi family) in the film Minari (2020). This research uses a sociolinguistic approach with a qualitative descriptive method. The data consists of transcripts of the Yi Family characters’ dialogues, which are analyzed through Spradley’s (1980) analysis stages, including Domain Analysis, Taxonomy Analysis, Component Analysis, and Cultural Theme Analysis. This analysis is used to map and classify language choices into three main communication domains: family, work, and society. Furthermore, to explain the variations found, the analysis was enriched with Janet Holmes’ (2013) Social Factors Theory, considering four elements: Participants, Setting, Topic, and Function. The results show that language choices within the Yi family are highly dynamic and situation-dependent, reflecting the process of cultural and linguistic assimilation in an immigrant context. The findings highlight the significant influence of the Setting (home vs public) and Participants’ generation (grandparents vs children) on the preference between Korean and English.
Keywords: Language Choice; Sociolinguistics; Minari Movie